Extended producer responsibility for waste tyres in the EU: Lessons learnt from three case studies – Belgium, Italy and the Netherlands. (15th April 2019) - Winternitz, Kim; Heggie, Mark; Baird, Jim
Highlights: In the EU, EPR for tyres mostly assigns physical and financial responsibility. EPR for tyres is no guarantee for environmentally most sound waste management. Recycling of waste tyres is more favourable for the environment than reuse. Cap on energy recovery helps achieving high recycling rate. EPR for tyres reduces flytipping and illegal stockpiling of tyres. Abstract: The article compares the performance of three Extended Producer Responsibility (EPR) systems for tyres and discusses the respective policy context that leads to these results. It aims to give insight into the varied implementation of EPR policy through the presentation of case studies. The EPR systems for tyres in Belgium, Italy and the Netherlands are described and common success factors as well as weaknesses are examined. The systems mainly differ in respect of scope and targets for material and energy recovery. The presented case studies assign physical (through a take-back obligation) as well as financial (through an advanced disposal fee) responsibility to the producers. EPR for tyres has been found to reduce flytipping and illegal stockpiling of tyres; increase resource efficiency by increased recycling; and move waste tyre management up the waste hierarchy. It is found that best results for recycling are achieved, if the legislation sets quantitative targets and clearly defines waste status of tyres to maximise local reuse/retread. It is argued however, that recycling is favourable over reuse/retread in the case of waste tyres. The case studies show that an EPR system is no guarantee for waste treatment in the most environmentally sound way. An EPR system will only achieve its objectives if properly designed, implemented and enforced. If legislation allows, Producer Responsibility Organisations will find the cheapest, not the environmentally most favourable, solution for waste management.